Thermal insulating products for building equipment and industrial installations. In-situ formed dispensed rigid polyurethane (PUR) and polyisocyanurate foam (PIR) products. Specification for the installed insulation products Part 2, (31st January 2013) - British Standards Institution
No abstract available